Specific effects of five subtypes of childhood maltreatment on suicide behaviours in Chinese adolescents: the moderating effect of sex and residence - Chang Peng; Junhan Cheng; Fajuan Rong; Yan Wang; Yafei Tan; Yizhen Yu (Epidemiology and Psychiatric Sciences, 2023)
Abstract Aims Although childhood maltreatment has been widely supported to be a robust predictor of suicide behaviours, the effects of different childhood maltreatment subtypes remain controversial and inconclusive. Moreover, whether the effects differ by sex in urban and rural adolescents is still unknown. This study aimed to quantify the associations between five subtypes of childhood maltreatment and different suicide behaviour involvement.